PERANCANGAN BATIK WONOGIREN DENGAN INSPIRASI MOTIF ISEN TATAHAN WAYANG KULIT GAYA SURAKARTA - Arianto Arianto; Sarah Rum Handayani; Theresia Widyastuti (Ornamen, 2022)
The tourism of batik and shadow puppets in Wonogiri Regency is quite potential to attract local and foreign tourists. This design is an effort to preserve beauty in Wonogiri and is expected to increase the diversity of Wonogiren Batik motifs to make it more attractive. The design method is through the stages of problem analysis, problem solving strategies, data collection, data sources, testing, and initial design ideas. The design results of this final project resulted in 6 batik designs with 2 realization designs. The batik motifs are taken from 6 motifs of isen inlaid wayang kulit Surakarta style which are applied in each design as the main motif and filler. Motive processing is supported by biomorphic patterns and abstractions as topographical representations of Wonogiri district. Two batik designs are made into primisima cotton cloth measuring 200cm x 115cm using handwritten batik techniques and coloring using remasol using the dabbing technique. The results of this design are applied as clothing textiles.